Connecting emotion to product customization: an integrated model system - Providência, B. (2012)
The act of seating is a good way of understanding the needs of user-centered design in connection to the final product. Several studies have explored the relation between pressure levels and the perceived comfort, or discomfort, of people in their relation with the seat (Schifferstein e Hekkert 2008). People with pressure ulcer problems usually do not have the opportunity to communicate with specialized technicians to obtain products that improve their quality of life. For this reason it is important to have integrated communication tools that permit the communication between people and technologies. This work aims to contribute towards an improvement of the well being of users with special needs, through the prevention of pressure ulcers. Based on collecting and communicating user information in an integrated system, that uses communication between the user and specialized technicians, to develop customized products supported by rapid fabrication technologies.